2012
DOI: 10.1167/iovs.12-10430
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Surface Extracellular DNA and Nuclease Activity Imbalance: A New Paradigm for Inflammation in Dry Eye Disease

Abstract: Extracellular DNA production and clearance mechanisms are dysregulated in DED. Nuclease deficiency in tear fluid allows eDNA and NETs to accumulate in precorneal tear film, and results in ocular surface inflammation. These findings point to novel therapeutic interventions in severe DED based on clearance of eDNA, NETs, and other molecular components from the ocular surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 58 publications
(65 reference statements)
3
82
0
1
Order By: Relevance
“…Furthermore, our group conceived independently the endogenous DNase activity assay used in this study; however, previous similar protocols were identified after literature research [25,26]. In conclusion, these evidences showed that the blood DNases are active in serum and the widely used anticoagulant EDTA also works as an indirect blood's DNase inhibitor that avoids ex vivo degradation of the ccfDNA.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, our group conceived independently the endogenous DNase activity assay used in this study; however, previous similar protocols were identified after literature research [25,26]. In conclusion, these evidences showed that the blood DNases are active in serum and the widely used anticoagulant EDTA also works as an indirect blood's DNase inhibitor that avoids ex vivo degradation of the ccfDNA.…”
Section: Discussionmentioning
confidence: 89%
“…3,[6][7][8] We have recently reported the role of NETs and eDNA as possible sources of inflammation in dry eye disease (DED), a chronic inflammatory disorder of the ocular surface. [9][10][11] We reported the presence of excessive amounts of eDNA and molecular components of NETs on the ocular surface of patients with DED, along with a deficiency of tear fluid nucleases, and we showed that eDNA abundance was highest in patients with severe DED. Also, we showed that treatment with recombinant human DNase I eye drops (rhDNase I; 0.1% four times a day) in patients with severe refractory DED and 5 excessive tear fluid eDNA resulted in symptomatic improvement, resolution of corneal rose bengal staining, and a reduction in tear fluid eDNA abundance.…”
Section: Introductionmentioning
confidence: 77%
“…9 We also performed experiments to evaluate whether in neutrophils that have been exposed to hyperosmolar stress, NETosis decreases when iso-osmolarity is restored. For these experiments, supernatant hyperosmolar culture medium was gently removed at 2 hours of incubation, new culture medium (iso-osmolar or hyperosmolar) was added, and neutrophils cultured for another 2 hours.…”
Section: Incubation Of Neutrophils For Netosis Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it was presented that limitation of NET formation using PAD inhibitors considerably affect lupus and atherosclerosis phenotype in murine models [18,19]. An imbalance between NETsderived eDNA production and nuclease efficiency is also observed in patients with dry eye disease, which results in ocular surface inflammation [20]. Additionally, increased NETosis also impairs wound healing in diabetes and treatment with plasma DNase 1 because the agent cleaving NETs was demonstrated as the approach to considerably improve re-epithelialisation in diabetic mice [21].…”
Section: Dna and F-actin Accumulation In Extracellular Compartmentmentioning
confidence: 99%